Plinthite and Its Associated Evolutionary Forms in Soils and Landscapes： A Review - EZE, P.N.; UDEIGWE, T.K.; MEADOWS, M.E. (Pedosphere, 2014)
At elevated temperature regimes and abundant precipitation, mobilization and accretion of weathered iron oxides are promoted especially in a reduced environments in the tropics. This may lead to the formation of plinthite, which hardens irreversibly upon repeated wetting and drying to form petroplinthite. The need for this review stems from the seemingly dearth of information on the subject and a need to clarify different terms used in describing plinthite. We review various research works on plinthite and its associated pedogenic forms in the tropics. Furthermore, we proffer recommendations as to the most appropriate land use management practices that could help minimise the environmental and agronomic problems associated with plinthite and its related pedogenic forms. Parent material, temperature, seasonality and geomorphology are critical factors that influence soil water regime which in turn affect the pedogenesis of plinthite. Soil pH and mineralogy are additional factors that could also promote plinthite formation. Fossil plinthic soils are potential proxies for palaeoenvironmental reconstruction. Measures used in the management of plinthic soils include mechanically breaking the hardpans and the use of organic and inorganic amendments to modify the structure and chemistry of the soils. Avoidance of practices that would predispose soils to erosion would also prevent plinthization. We call for the relinquishment of the term ＂[aterite＂ which is a generM term for all forms of iron oxide-enriched earthy materials as used for plinthite. Plinthic horizon should also be incorporated into the United States Department of Agriculture Soil Taxonomy in view of its growing importance in soils.